Risk Factors for Hypertension in the Coastal Area of Tarakan City - Najihah; Dewi Wijayanti; Tukan, Ramdya Akbar; Arifin, Hidayat; Suhermi (Window of Health : Jurnal Kesehatan, 2024)
Hypertension is a severe medical condition and is the leading cause of premature death worldwide, significantly increasing the risk of heart, brain, kidney, and other diseases. However, not all people with hypertension are aware of their disease, and it is only discovered after complications occur. Therefore, hypertension must be prevented and controlled. Prevention and control of hypertension aims to prevent and reduce the probability of morbidity, complications, and death. Hypertension can be prevented by controlling risky behaviors. This study aims to analyze the risk factors for hypertension in coastal communities in Tarakan City. This research is quantitative research with a cross-sectional study design. The study sampled people in the working area of the Amal Beach Health Centre, Tarakan City, and met the sample criteria obtained using a purposive sampling technique. The data obtained will be processed univariate and bivariate. The results showed that there was a significant relationship between obesity (p-value 0.001), family history (p-value 0.013), and sports activity (p-value 0.009) with the incidence of hypertension. Smoking habits did not show a significant relationship (p-value 0.230) with the incidence of hypertension. This study concludes that obesity, family history, and exercise activity are risk factors for the incidence of hypertension in coastal areas of Tarakan City. Therefore, it is hoped that health promotion efforts in the form of scheduled counseling on risk factors for hypertension and preventive efforts in the form of early detection so that people can prevent or control hypertension to avoid complications.